Induction for classic laryngeal mask airway insertion: Does low-dose fentanyl work? - Akanksha Dutt; Anjum Khan Joad; Mamta Sharma (Journal of Anaesthesiology Clinical Pharmacology, 2012)
Background : Laryngeal mask airway (LMA) insertion requires an optimal balance of anesthesia. Propofol with different opioids is a preferred combination. Two doses of fentanyl were compared for the efficacy and side effects. Materials and Methods: 96 patients were randomly distributed into F 1 (fentanyl 1 mcg/kg) and F 2 (fentanyl 2 mcg/kg) groups. The conditions for LMA insertion, hemodynamic profile, bronchoscopic view, and incidence of sore throat were compared. Result: There was no statistically significant difference in any parameter in the two groups except for a significant fall in systolic and mean arterial pressure in F 2 group. Conclusion: Both doses of fentanyl (1 and 2 mcg/kg) provide comparable insertion conditions for LMA. Fentanyl in the lower dose provides a more stable hemodynamic profile.